Evaluation of Performance-Based Assessment Principles in the Teaching Factory Environment: A Systematic Literature Review - Labusab Labusab (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study systematically reviews the implementation of performance-based assessment (PBA) principles in Teaching Factory (TeFa) environments within vocational education. Drawing upon peer-reviewed publications from 2015–2025, the study synthesizes empirical and conceptual research that explores how validity, reliability, authenticity, and objectivity are operationalized in performance assessments. The review follows the PRISMA framework, involving database searches across Scopus, ERIC, Google Scholar, and national repositories. Findings indicate that digital assessment systems, rubric-based evaluation, and collaborative validation processes contribute significantly to improving the quality of PBA in TeFa. Nevertheless, challenges persist in maintaining contextual authenticity and inter-rater reliability across diverse institutional and industrial settings. The review concludes with implications for integrating digital technologies and standardized rubrics to enhance assessment fairness and transparency in vocational education.